Tapestries of hope: film, youths and HIV/AIDS in Zimbabwe and South Africa - Rwafa, Urther; Rafapa, Lesibana (Commonwealth Youth and Development, 2016)
In Zimbabwe, the marauding effects of the human immunodeficiency virus and acquired immunodeficiency syndrome (HIV/AIDS) are felt in almost all families, among different age groups, class lines, races and creed. The effects are debated and discussed, and different intervention measures are suggested using various forms of media. The communication-science-based interventions and advocacy promoted through film are an integral part of biomedically based scientific research into understanding the nature and manifestations of HIV/AIDS. However, it is worrisome that in most of the research, debates and discussions that focus on HIV /AIDS, adults take the centre-stage. This practice of speaking for youths, and not to and with them, denies the reality that youths are agents of social change whose ‘‘voice’’ and action can have the capacity to transform society for the better in the face of HIV /AIDS. In Zimbabwe, one methodological approach that youths can use to debate and spread the message about the devastating effects of HIV/AIDS is film. In the Zimbabwean section, this article singles out the short film The sharing day (2009) as an informative and communicative tool that features youths dramatising narratives of hope, pain and sorrow as they are confronted by the reality of HIV/AIDS. In the South African section of the article, the abcnews.com documentary (2001) on Xolani Nkosi Johnson’s struggle with HIV/AIDS is used to signal hope. The article critiques documentary filmmaking on Johnson, using criteria such as youth involvement (Harrison et al. 2010; Wang 2006), effectiveness of the message (Hanan 2009) and bonding and bridging social capital (Foulis et al. 2007).